Eksistensi Pusat Organisasi Kemasyarakatan (POK) Masyarakat Menyikapi Pemilu 2024 - Lilis Purba; Medrys Selan; Ibnu Mubarok (LPPM Iblam School of Law, 2024)
General Elections (Pemilu) in Indonesia are a concrete manifestation of democratic values, in line with Pancasila and the 1945 Constitution. Since its first implementation in 1955, the Pemilu has undergone several evolutions in its legal aspects, stages, and administration. In anticipation of the 2024 Pemilu, new dynamics have emerged, including changes in technology and the political preferences of society. A key element in this electoral landscape is the Center for Community Organizations (POK). This research highlights the role and existence of POK in facing the challenges of the 2024 Pemilu. Through a basic theoretical study method with a qualitative approach, this research examines the position, role, and challenges faced by POK in the context of Indonesian democracy. The results show that POK plays a vital role as a mediator between the community and government officials, with high expectations to actively ensure fairness and integrity in the 2024 Pemilu.